Consumer trust and its effect on sustainable e-commerce development in China. (24th February 2006) - Hynes, Niki; Gurau, Calin; Chan, Henry W.K.
Whilst China is the largest single world economy, e-commerce has been relatively slow to develop, especially within consumer markets. In more advanced e-economies such as the USA the switch between traditional retail sales and e-sales is growing all the time and is predicted to be as high as 10%. If only a small percentage of retail sales in China were switched to e-commerce, the potential market in China is immense. In addition, in terms of international competitiveness, the risks of not participating in what is such an increasing important global arena are also high. Therefore, the development of a long term and sustainable e-commerce environment is of great importance to China's economy. Whilst there are many practical reasons why e-commerce development has been slow, this study examines the barriers from a consumer's perspectives using empirical data collected from Chinese consumers via the internet.